Biology and fisheries aspects of Western Longnose Spurdog, Squalus edmundsi from the Eastern Indian Ocean, Indonesia - FAHMI FAHMI; AGUS ARIFIN SENTOSA (Society for Indonesian Biodiversity, 2017)
Fahmi, Sentosa AR. 2017. Biology and fisheries aspects of Western Longnose Spurdog, Squalus edmundsi from the Eastern Indian Ocean, Indonesia. Biodiversitas 18: 1714-1722. A research has been done to determine some biological aspects of Western Longnose Spurdog (Squalus edmundsi) from the Eastern Indian Ocean Fishing Region in Indonesia (WPP 573). A total of 1797 samples were recorded from bottom longline fisheries at Tanjung Luar, Lombok from July 2015 to November 2016 by a trained enumerator. The study revealed that Selat Alas and the south west of Sumbawa waters are the most fished areas in the region for this species, with the peak fishing season may occur from January to March. The average catch rate of S. edmundsi was about 8 individuals per boat. The size of sharks varied from 470 mm to 1150 m total length (TL), with average size was 723.6Â±111.5 mm. Size distributions and sex ratio between females and males were significantly different, indicating a sexual dimorphism. This study revealed a fact that there was no seasonal pattern in the reproductive cycle of S. edmundsi in this region, which means the parturition may occur throughout the year. Analysis on its population status showed that this species was very susceptible to overfishing. This condition should be responded by the government through management actions for its fishery.